Bleeding, Vertebral Fractures and Vascular Calcifications in Patients Treated with Warfarin: Hope for Lower Risks with Alternative Therapies - Fusaro, Maria; Crepaldi, Gaetano; Maggi, Stefania; D'Angelo, Angela; Calo, Lorenzo; Miozzo, Davide; Fornasieri, Alessandro; Gallieni, Maurizio (Current Vascular Pharmacology, 2011)
Anticoagulant therapy in patients with atrial fibrillation requires careful evaluation because its benefits i.e. prevention of thromboembolism, must be greater than the risk of bleeding. Patients at higher risk of thrombosis are evaluated through specific scores, such as the CHA2DS2VASc, coupled with scoring systems for assessing bleeding risks, such as the HAS-BLED score. In addition to bleeding, other risks have been associated with the use of warfarin, including an increased susceptibility to vascular calcifications and fractures caused by a reduction in the levels of vitamin K dependent carboxylated enzymes, matrix Gla-protein (MGP) and bone Gla-protein or osteocalcin (BGP). In fact, while on one side warfarin is used to prevent embolism, on the other hand acting as a vitamin K antagonist it blocks the inhibitory effect of MGP on vascular calcification. Similarly, patients treated with warfarin carry a greater risk of developing osteoporosis and fractures, due to reduced BGP activity. Recently, a new generation of anticoagulant drugs has been developed, such as dabigatran, a direct thrombin inhibitor, and rivaroxaban, a direct factor-Xa inhibitor. They offer an interesting alternative to warfarin, because they do not require frequent blood tests for monitoring while offering similar results in terms of efficacy. Lacking the inhibitory effect on the vitamin K cycle, the consequent side effects can be avoided. If, compared to warfarin treated patients, a lower incidence of vascular calcifications and fractures will be demonstrated, the advantages over warfarin may be even greater, leading to further benefits in terms of morbidity and mortality.
Keywords: thromboembolism